Lead Poisoning in an Infant: A Case Report - Anahita Alizadeh; Anoush Azarfar; Yalda Ravanshad (Mashhad University of Medical Sciences, 2016)
There is inadequate knowledge about acute poisoning as a common problem in children. Acute poisoning in children, , is one of the health problems, requiring immediate treatment. Case report: A two-month-old male infant with discoloration of the nails was admitted to the Emergency Pediatric Unit of Imam Reza Hospital, Mashhad, Iran in 2014. Following clinical evaluations, the blood lead level was determined to be high. The cause of neonatal condition was a traditional medicine, applied by the mother for the treatment of dermatitis in the infant. The lead concentration was high in this medicine, thus resulting in neonatal lead poisoning. Conclusion: It is obvious that medicinal drugs should be used cautiously for children, especially infants. Also, drug characteristics and the process of production should be precisely specified. In fact, without taking precautions, any medicinal drug or substance could have various adverse effects on pediatric populations.